Understanding vehicle consent search requests through the use of the social conditioning model and illusory correlation - Waldspurger, Ella (International journal of police science & management, 2023)
Previous studies show racial or ethnic bias in police decision-making for consent search requests. Yet, few studies apply the social conditioning model and illusory correlation to explain an officer's decision-making for requesting consent to search the driver's vehicle. Furthermore, a potential consideration when using this theory has not considered the possible explanation that the officer may also conduct such a request because the officer views the citizen as “out-of-place”. This study uses Illinois traffic stop data from 2016 to 2018 for municipal agencies with a minority representation of less than one (i.e., less-diverse police department and a greater chance that the officer involved in the stop is White) and includes one measure from the 2016 Law Enforcement Management and Administrative Statistics. Utilizing propensity score matching to match the drivers based on race/ethnicity and gender, the current findings show that non-White drivers and non-White male drivers, who are stopped by police serving predominately White areas and who serve in a less-diverse police department, are more likely to have an officer request consent to search their vehicle. These findings are consistent with racial profiling and support the social conditioning model and illusory correlation as an appropriate theoretical explanation for police officers. Moreover, the officer's decision-making could be based on an individual driver stopped by an officer serving a predominately White community and interacting with a less-diverse police department. The officer may view the minority driver as being “out-of-place”, which is an additional reason for the officer to request consent to search the minority driver's vehicle.